Pembuatan Template Desain Publikasi Desa Tambakcemandi Sidoarjo - Jerricho Ivandro Ekklesia; Rifdah Rohadatul Aisy; Rr. Tsabitah Phalozaky A.P; Shahnez Annisa Mekoa; Aaliyah Viorella Nada Tamtama; Suprihatin; Riesta Ayu Oktarina (LPPM Stikosa - AWS, 2024)
Tambakcemandi is a village in Sedati District, Sidoarjo Regency, East Java Province, Indonesia. The Tambakcemandi Village area is located in a lowland area with an area of 858.309 ha, as a student of Communication Science we realize how important a good communication process is from the Communicator to the Communicator, so we Team 2 KKL Stikosa-AWS are interested in applying our knowledge in Visual Communication Science. The purpose of this activity is to help the Tambakcemandi Village Hall to apply the Administrative Flow attractively, so that the community can more easily understand the information provided by the Tambakcemandi Village Hall. Team 2 KKL Stikosa-AWS first determined the KKL place in Tambakcemandi, after that we formed a KKL Program that could be realized in Tambakcemandi, after getting approval from the Tambakcemandi Village Hall, we then formed a schedule. The results of the activities achieved during the Field Work Lecture are Team 2 KKL Stikosa-AWS can make template designs for Tambakcemandi Village Hall, Posyandu and Poslansia.